2016
DOI: 10.1158/1940-6207.capr-15-0307
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Inflammatory Markers and Risk of Advanced Colorectal Adenoma in Women

Abstract: Evidence remains inconclusive about the association of systemic inflammatory markers with colorectal neoplasia. We investigated whether circulating inflammatory markers were associated with risk of advanced colorectal adenoma. We measured plasma macrophage inhibitory cytokine-1 (MIC-1), C-reactive protein (CRP), interleukin-6 (IL-6), and soluble tumor necrosis factor receptor 2 (sTNFR-2) in blood samples drawn from 32,826 women in 1989-1990 in the Nurses' Health Study. Through 2008, we documented 757 cases of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 55 publications
2
24
2
Order By: Relevance
“…However, the limited information precluded a more robust assessment of the above-mentioned findings. The pooled results on CRP and IL-6 and risk of colorectal adenomas are consistent with those from nested case-control studies [ 8 , 17 , 23 ] in which circulating levels measurement preceded colorectal adenomas incidence. No nested case-control study on circulating levels of TNF-α and colorectal adenomas was identified.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…However, the limited information precluded a more robust assessment of the above-mentioned findings. The pooled results on CRP and IL-6 and risk of colorectal adenomas are consistent with those from nested case-control studies [ 8 , 17 , 23 ] in which circulating levels measurement preceded colorectal adenomas incidence. No nested case-control study on circulating levels of TNF-α and colorectal adenomas was identified.…”
Section: Discussionsupporting
confidence: 81%
“…The departure from a linear relationship was not significant between CRP (P for nonlinearity =0.18), IL-6 (P for nonlinearity =0.35) and TNF-α (P for nonlinearity =0.87) and risk of colorectal adenoma, respectively. The risk of colorectal adenomas increased by 2% [1.02 (0.97-1.08)] for each 1 mg/L increment in circulation CRP levels (eight studies [ 8 , 10 , 17 , 20 , 22 25 ] including 4,981 cases), 9% [1.09 (0.91-1.31)] for each 1 ng/L increment in circulation IL-6 levels (five studies [ 8 , 13 , 15 , 20 , 25 ] including 1,763 cases), and 6% [1.06 (0.93-1.21)] for each 1 pg/mL increment in circulation TNF-α levels (four studies [ 12 13 , 18 , 25 ] including 1,452 cases), respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In humans, MIC-1/GDF15 serum levels rise when adenomatous polyps develop, rise further in proportion to the stage and extent of colon cancer, and predict the cancer outcome (Brown et al, 2003;Danta et al, 2017;Song et al, 2016;Chen et al, 2017;Mehta et al, 2015;Li et al, 2016) (Figure 3). Further, a coding region H6D polymorphism in mature MIC-1/GDF15 alters colorectal cancer behavior and risk (Brown et al, 2003;Wang et al, 2015a).…”
Section: Mic-1/gdf15 In Mitochondrial Dysfunction and Diseasementioning
confidence: 99%
“…Grouping studies by fasting status and measurement method showed statistically significant results when considering studies that collected fasting blood samples (OR = 1.38, 95%CI: 1.02-1.88; I 2 = 32%, P heterogeneity = 0.21) and INA measurement (OR = 1.54, 95%CI: 1.06-2.23; I 2 = 29%, P heterogeneity = 0.24). Moreover, including one study[23] in which blood analyses were not uniformly conducted on fasting samples but risk estimates were adjusted for fasting/non-fasting, did not change markedly results (OR = 1.29, 95%CI: 1.01-1.64; I 2 = 25%, P heterogeneity = 0.25). No significant confounders were detected when grouping by gender, sample size, geographical location, and quality score.…”
Section: Resultsmentioning
confidence: 98%